Oral health related quality of life of children ages 8-10 years old in Aurora A. Quezon Elementary School A cross-cultural adaptation of child-oral impact on daily performance index in Philippine setting - Gomez, Krystark A.
Oral health related quality of life (OHRQOL) is a fast growing concept that seeks to understand how oral diseases affect the quality of life of people. However, here in the Philippines, the concept is still new especially in the field of pediatrics. There is a necessity to come up with an index that could be utilized to evaluate the OHRQOL of children here in the Philippines. The study aims to adapt the Child-Oral Impact on Daily Performance (C-OIDP), an OHRQOL index, in the Philippine setting, among Filipino children ages 8-10 years old. METHODS: A descriptive study consisting of a cross-cultural adaptation, forward/backward translation and a pilot study of the C-OIDP index was done. A total of 136 students from Aurora A. Quezon Elementary School (AAQES) participated in the study. RESULTS: The C-OIDP scores showed that the daily performance of eating (54.41%) had the greatest impact on these students which had toothache (20.55%) as the most perceived cause. The most prevalent oral issue is tooth color (66.91%). CONCLUSION: Generally, the students of AAQES have a high Oral Health-Related Quality of life. This study further needs validation and a higher population.